Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar IPA Kelas VI - Ahmad Marwan (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
This research aimed to examine the effect of guided inquiry learning model toward student learning outcomes at adaptation of living things of elementary school. The first group taught by using guided inquiry learning and the second group taught by conventional models. Data were analyzed with t-test of significant level α = 0.05. The result of the research shows that the result of t-test analysis ( analisis uji–t) is t-hitung bigger than ttabel (t-hitung 4,193 > t-tabel 2,145) with 5% significant level, this means there is significant difference of IPA learning result between student which is taught by guided inquiry learning models assisted concept mapping with students who were taught by direct instruction model. The results show that there is no influence of guided inquiry learning models on student learning outcomes